(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The current research aims to identify the effectiveness of social stories in increasing social interaction among children with an autism spectrum disorder. The researcher used the single-subject design methodology (Single Subject Designs, SSD) with (A-B) design to answer the research questions. The study sample consisted of (3) children with autism spectrum disorder enrolled in a transit daycare center in the Asir region, Saudi Arabia. The results of the study showed that there is a positive functional relationship between social stories and play to increase social interaction among children with autism spectrum disorder, which contributed to the acquisition and generalization of this behavior. It may not be adequate to the desired degree, which calls for recommending a study that measures the effectiveness of the intervention in children with autism spectrum disorder accompanied by hyperactivity and attention deficit.